Probabilistic based design for connecting links in single point mooring system subjected to dynamic spectral fatigue line tension - Koothayan, Yugabalan (2005)
Structural reliability theory has been applied to design structural members. A major goal is to achieve a balance between safety and cost (or weight) for a given safety level. It is therefore desirable that optimum design is achieved through probabilistic based design procedures. This study is concerned with optimum design of connecting links frequently found in a single point mooring system, based on probabilistic based design at the component level. Single point mooring systems are subjected to fatigue loading due to environment conditions. The study considered a single point mooring system located in Volve Field in the North Sea, offshore Norway. With the existing deterministic design basis, the probabilistic based design is performed using the design parameters obtained from the design codes used in the deterministic design. The results of probabilistic based design output are checked against the deterministic based design output. The probabilistic based results are obtained from Monte Carlo simulation where the basic input in the Transfer Function value which was obtained from deterministic Finite Element Analysis. As a conclusion, the fatigue life values for the connecting links obtained are compared based on the design method. Through this research study, it has been proved that an economical and safe structure can be designed using probabilistic design method, with respect to fatigue loading. This method can be implemented in the engineering stage.